KAPASITAS ORGANISASI DINAS PERTANIAN TANAMAN PANGAN DAN HORTUKULTURA PROVINSI JABAR DALAM PENGEMBANGAN BENIH PADI INDUK - Mohammad Iqbal; Rita Myrna; Elisa Susanti (JANE - Jurnal Administrasi Negara, 2023)
One aspect of the low achievement of parent rice seeds is due to the capacity of the Department of Agriculture for Food Crops and Horticulture of West Java Province in carrying out their duties to reproduce rice seeds that are not optimal. This research aims to see the capacity of the Department of Agriculture, Food Crops and Horticulture, West Java Province. The aspects used in this descriptive qualitative research are (1) personnel, (2) infrastructure, technology, and financial resources, (3) strategic leadership, (4) program and process management, and (5) networking and linkages. Salah satu aspek rendahnya pencapaian benih padi induk diakibatkan kapasitas Dinas Pertanian Tanaman Pangan dan Hortikultura Provinsi Jawa Barat dalam melakukan tugasnya dalam rangka memperbanyak benih padi belum optimal. Tujuan dilakukan penelitian ini guna melihat Kapasitas Dinas Pertanian Tanaman Pangan dan Hortikultura Provinsi Jawa Barat. Aspek yang digunakan dalam riset kualitatif deskriptif ini yakni( 1) personnel ( sumber daya manusia), (2) infrastucture, technology, and financial resources (infrastruktur, teknologi, serta sumber daya keuangan), (3) strategic leadership (kepemimpinan strategis), (4) program and process management (program serta manajemen proses), serta (5) networking and linkages (jejaring kerjasama serta ikatan dengan pihak lain).